Micro-nanoelectronics devices modeling of diffusion and operation processes - Gontrand, Christian (ISTE Press, 2018)
Micro-nanoelectronics Devices: Modeling of Diffusion and Operation Processes concentrates on the modeling of diffusion processes and the behavior of modern integrated components, from material, to architecture. It goes through the process, the device and the circuit regarding today's widely discussed nano-electronics, both from an industry perspective and that of public entities